-3(5+7p)=5(-2p+8)

Simple and best practice solution for -3(5+7p)=5(-2p+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(5+7p)=5(-2p+8) equation:



-3(5+7p)=5(-2p+8)
We move all terms to the left:
-3(5+7p)-(5(-2p+8))=0
We add all the numbers together, and all the variables
-3(7p+5)-(5(-2p+8))=0
We multiply parentheses
-21p-(5(-2p+8))-15=0
We calculate terms in parentheses: -(5(-2p+8)), so:
5(-2p+8)
We multiply parentheses
-10p+40
Back to the equation:
-(-10p+40)
We get rid of parentheses
-21p+10p-40-15=0
We add all the numbers together, and all the variables
-11p-55=0
We move all terms containing p to the left, all other terms to the right
-11p=55
p=55/-11
p=-5

See similar equations:

| 331/7=x | | (2y-4)-y=14 | | -16=2(-3x+4 | | 10(-x+8)=20 | | 2(6r-5)+4r=-2(1-2r)-8 | | -4(z-3)=-4 | | 2x-15+2x+20+x=180 | | -22+13=m-1 | | 6x-4)=3x+1 | | 105-25-3b=45-1 | | 10x-(2x=)=-3(15-4x) | | -6n-12=-1-6(n+5) | | -21+24=m-8 | | V-1-6v=2(v+4)-3(8v+3) | | 10=c–2 | | 10-29r+30=40-20r-4r | | x6.2=2.2+x | | 3x+1-2x=4 | | 5n-6(6+2n)=-4(n-1)+2 | | X2+34=10x | | 63*8/x+41=55 | | 0.25(8s-4)=s+8-2s | | 13-2x=-15 | | 14x^2-11x-60=0 | | 3v–1=5 | | 1+2y+7y=19 | | 6x2+7x-20=0 | | 4+a=2a+3 | | 21=6(1-7p)+3(7p+5) | | 8x+15x=3x-20 | | 3s+50=10s-62 | | 9p–12p=-15 |

Equations solver categories